2014
DOI: 10.1080/02626667.2014.889296
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-ecology of groundwater-dependent ecosystems: applying basic science to groundwater management

Abstract: Effective policies to protect groundwater-dependent ecosystems require robust methods to determine the environmental flows and levels required to support species and processes. Frameworks to support groundwater management must incorporate the relationships between hydrology and species and ecological processes. These hydro-ecological relationships can be used to develop quantitative, measurable thresholds that are sensitive to changes in groundwater quantity. Here we provide a case study from a group of fens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 57 publications
1
38
0
1
Order By: Relevance
“…Aquatic environments that rely on the flow or chemical characteristics of groundwater are collectively known as groundwater‐dependent ecosystems (Aldous & Bach, ; Aldous & Bach, ; Rohde, Froend, & Howard, ). This definition recognizes the pivotal role of groundwater in underpinning ecological communities associated with streams, rivers, springs, and wetlands, as well as with underground caves or phreatophyte ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic environments that rely on the flow or chemical characteristics of groundwater are collectively known as groundwater‐dependent ecosystems (Aldous & Bach, ; Aldous & Bach, ; Rohde, Froend, & Howard, ). This definition recognizes the pivotal role of groundwater in underpinning ecological communities associated with streams, rivers, springs, and wetlands, as well as with underground caves or phreatophyte ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Defining water needs for wetlands is challenging, because the term wetlands embraces many different ecosystem types that may have very different hydrological characteristics, even when they are geographically close to each other (de la Hera and Murillo 2014). Aldous and Bach (2014) found that, for fens in Oregon, USA, water table depth is the critical issue rather than river flow, with a required water table within 35 cm of the surface. Hendriks et al (2014) reported that drainage and groundwater abstraction in sandy catchments in the Netherlands meant that low flows were reduced below the environmental flow criterion, whilst Kennen et al (2014) found that groundwater abstraction led to a 20% reduction in intolerant macro-invertebrates in New Jersey, USA, due to reduced river flow.…”
Section: Historical Contextmentioning
confidence: 99%
“…Other factors such as land cover, land use practices, surface water dynamics, and water quality are important for the characterization of the response of GDEs [44], evaluation of the impacts of natural events and anthropogenic actions on GDEs [17,20,45], and for estimating the volume of groundwater required by GDEs [46]. However, these factors are not included in our simplified model framework.…”
Section: Study Areamentioning
confidence: 99%